Discrimination and competition in online microfinance lending – evidence from www.kiva.org. - Luong, Ngoc Tram. (2012)
Financial services with the help of modern technology are no longer an exclusive privilege to the high-class individuals and businesses but also to the poor. Through the emergence of microfinance, funds from charitable sources can be transferred toward the poor as altruistic acts. In this paper the lending activities on www.kiva.org are examined on the basis of loan information and picture-based perceptions on various physical and subjective characteristics to determine the existence and magnitude of lenders’ discrimination and whether competition can help reduce it. We found out that discrimination exists as people in general prefer to lend money to female, younger, more attractive, less obese borrowers and to those look more honest. We also observed an anomaly in the coefficient for creditworthiness, that borrowers who are perceived to be more creditworthy are less favoured. Regarding the effect of competition, a very interesting finding is that not only are male borrowers less favoured than their female fellows but competition, instead of reducing prejudice as predicted by Becker and Arrow (Becker, 1957) (Arrow, 1973), makes male borrowers do even worse. We concluded that although competition in general helps facilitate time to funding for all loans, it does not significantly reduce discrimination at all as expected by theory.